A coordinated scheduling of delivery and inventory in a multi-location hospital supplied with a central pharmacy - Zakaria Hammoudan; Olivier Grunder; Toufik Boudouh; Abdellah ElMoudni (Logistics Research, 2016)
In today's manufacturing outlook, coordinated scheduling of delivery and inventory represents a leading leverage to enhance the competitiveness of firms which aims to address the new challenge coming from scheduling problems. Though in the last decades this kind of issue has been extensively approached in the literature, a set of constraints and compulsory dispositions strongly increases the complexity of the considered problem. Actors of the pharmaceutical supply chain have to meet various global regulatory requirements while handling, storing and distributing environmentally sensitive products. The studied problem in this paper focuses on a real-case scheduling problem in a multi-location hospital supplied with a central pharmacy. The objective of this work is to find a coordinated production and delivery schedule such that the sum of delivery and inventory costs is minimized. A mixed-integer programming formulation is first detailed to consider the problem under study. Then, a branch-and-bound algorithm is proposed as an exact method and a dedicated heuristic algorithm is highlighted to solve the problem. At last, the experimental results show the efficiency of the proposed solving methods, based on the two following criteria: solution quality and processing time.
Keywords: 650; Case study; Coordinated scheduling; Production and transportation; Mixed-integer programming; Branch and bound; Heuristic algorithm